Uji Aktivitas Krim Tabir Surya yang Mengandung Ekstrak Etanol Alga Coklat (Sargassum sp.) - Rosidah, Sofiatun; Sayekti, Endah; Rahmalia, Winda (Jurnal Ilmiah Farmasi, 2026)
Background: Sunscreen protects the skin against ultraviolet (UV) radiation, particularly UVB, which is a major contributor to skin damage. Brown algae (Sargassum sp.) are rich in phenolic antioxidant compounds with potential as natural sunscreen agents. However, research on the incorporation of ethanolic extracts of Sargassum sp. into topical cream formulations and on the evaluation of both their photoprotective activity and formulation stability remains limited. This study therefore offers a fresh perspective on the dual role of brown algae extracts as natural sunscreen ingredients and stabilizing components in cosmetic preparations.Objective: This study aims to develop a cream formulation containing the ethanolic extract of Sargassum sp. and to evaluate its sunscreen activity.Method: The extract was obtained by maceration using 96% ethanol and subsequently subjected to phytochemical analysis. Cream formulations were prepared with six concentrations of the extract (0, 0.07, 0.13, 0.20, 0.27, and 0.43%) and evaluated for homogeneity, pH, spreadability, and in vitro Sun Protection Factor (SPF) using a UV-Vis spectrophotometer.Results: All cream formulations were stable, homogeneous, and exhibited pH values between 4.7 and 5.8, consistent with SNI 16-4399-1996 standards. The highest SPF value was observed in the 0.43% formulation, reaching 6.234 ± 0.503, which is categorized as extra protection. The sunscreen activity is attributed to phenolic compounds in the extract, which possess both antioxidant properties and UV-absorbing capacity.Conclusion: Sunscreen cream formulations containing the ethanolic extract of Sargassum sp. met the required physical stability standards. SPF testing revealed that the 0.43% extract formulation (KTS5) produced the highest SPF value, 6.234 ± 0.503, which is classified as extra protection and indicates optimal sunscreen activity.